Biological Evaluation of Some Plant Bioactives as Feed Additives to Replace Antibiotic Growth Promoters in Broiler Feeds - Arnold Parlindungan Sinurat; Tiurma Pasaribu; Tresnawati Purwadaria; Tuti Haryati; Elizabeth Wina; Tri Wardhani (Jurnal Ilmu Ternak dan Veteriner, 2020)
Antibiotics (AGP) have been used as feed additives to promote growth and feed efficiency in poultry production. However, many countries include Indonesia now ban the use of AGP and attempts are made to replace the antibiotic to maintain good performances of broilers. Plant bioactives is one of the alternatives that could replace the AGP. An experiment was conducted in an attempt to replace the AGP in broiler feed with a mixture of some plant bioactives (liquid smoke of cashew nutshell, Phyllanthus niruri, and clove leaves). Eight (8) dietary treatments were formulated to have similar nutrients consist of negative control (NC), positive control (NC+AGP), diets supplemented with liquid plant bioactives in 3 levels and diets supplemented with powder plant bioactives in 3 levels.  Each diet was fed to 6 replications of 10 birds each from 1 to 35 days old. The performances and the immune response of the broilers due to the treatments were observed. Results showed that the powder plant bioactives could not improve the performance of broilers. None of the feed additives (AGP or plant bioactives) affect the immune systems of the broilers. However,  liquid plant bioactives in low dose improved the performance of broilers better than the AGP and therefore is suitable to replace the antibiotic as feed additives in broiler diet.